Free-beam soliton self-compression in air. (17th January 2018) - Voronin, A A; Mitrofanov, A V; Sidorov-Biryukov, D A; Fedotov, A B; Pugžlys, A; Panchenko, V Ya; Shumakova, V; Ališauskas, S; Baltuška, A; Zheltikov, A M
Abstract: We identify a physical scenario whereby soliton transients generated in freely propagating laser beams within the regions of anomalous dispersion in air can be compressed as a part of their free-beam spatiotemporal evolution to yield few-cycle mid- and long-wavelength-infrared field waveforms, whose peak power is substantially higher than the peak power of the input pulses. We show that this free-beam soliton self-compression scenario does not require ionization or laser-induced filamentation, enabling high-throughput self-compression of mid- and long-wavelength-infrared laser pulses within a broad range of peak powers from tens of gigawatts up to the terawatt level. We also demonstrate that this method of pulse compression can be extended to long-range propagation, providing self-compression of high-peak-power laser pulses in atmospheric air within propagation ranges as long as hundreds of meters, suggesting new ways towards longer-range standoff detection and remote sensing.